Thrombolytic therapy and nursing management of a patient with hemichorea-hemiballismus caused by acute cerebral infarction (1例急性脑梗死致偏侧舞蹈症的溶栓治疗和护理体会) - XIAO Zhouhua (肖周华); YAO Weiling (姚卫灵); WANG Xin (王欣) (Association of Integrative Nursing, 2024)
Hemichorea-hemiballismus caused by cerebrovascular disease has been reported in many literatures, but it is rare in clinic. It is necessary to enhance the vigilance of clinicians. Based on the intravenous thrombolytic therapy, a comprehensive nursing plan including vital signs monitoring, safe protection, and prevention of fall and disease recurrence should be carried out to improve the curative effect and prognosis of such patients. (脑血管病致偏侧舞蹈症临床少见, 若诊治不当可能延误治疗, 加重病情。急性脑梗死并发偏侧舞蹈除静脉溶栓治疗外, 还应密切观察患者生命体征, 做好安全防护, 防止跌倒、疾病复发等不良事件。)